Portrayal of Women’s Objectification in Sending the lord away by Nasira Sharma - Padma Dewi Kalingga; Febry Aulia Hijazi (Morphosis: Journal of Literature, 2024)
This research discusses the short story Sending the Lord Away by Nasira Sharma, which provides an overview of an Indian Muslim woman who lives in a patriarchal society that limits women in determining their future. Therefore, Farzana tries to break the stereotype of women who have been positioned as passive objects who are subject to male domination and distortion of religion as a rule that binds women. This research uses descriptive qualitative methods by collecting data through stories. In this research the theory used is through a feminist perspective that focuses on the principle of ’the others’ , especially the objectification of women initiated by Simone de Beavoir. On the other hand, this research also uses the concept of the theory of objectification by Marta Nussbaum in examining the actions of families and men who limit women with the shield of religion and marriage. Through this research it can be seen that Nasira Sharma shows the position of women in this short story trapped in the patriarchal system. Women are placed as inferior and subordinate objects in every aspect of life by limiting their choices and twisting religion as a shield by men. Keyword: Women, Objectification, Patriarchy, Male domination.